Molecular confirmation of species status for the allopolyploid cotton species, Gossypium ekmanianum Wittmack. - Grover, C. E. (2014)
Understanding the relationship between domesticated crop species and their wild relatives is paramount to germplasm maintenance and the utilization of wild relatives in breeding programs. Recently, Gossypium ekmanianum was resurrected as an independent species based on morphological analysis of specimens obtained from the Dominican Republic, where the original type specimen was collected. The molecular data presented here support the recognition of G. ekmanianum Wittmack as a distinct species that is phylogenetically close to G. hirsutum L. Analyses of chloroplast DNA data reveal species-specific, indel polymorphisms that unambiguously distinguish G. ekmanianum samples from other polyploid congeners. Furthermore, analysis of accessions that originated from the Dominican Republic demonstrate the cryptic inclusion of this sister taxon within the US National Plant Germplasm System, a germplasm collection maintained for diversity preservation and future breeding resources. The data presented here indicate that ‘‘wild’’ G. hirsutum accessions may include the closely related G. ekmanianum, and provide a method to easily distinguish the two.